Uncovering hidden heterogeneity: Geo-statistical models illuminate the fine scale effects of boating infrastructure on sediment characteristics and contaminants. Issue 2 (30th June 2017) - Hedge, L.H.; Dafforn, K.A.; Simpson, S.L.; Johnston, E.L.
Abstract: Infrastructure associated with coastal communities is likely to not only directly displace natural systems, but also leave environmental footprints' that stretch over multiple scales. Some coastal infrastructure will, there- fore, generate a hidden layer of habitat heterogeneity in sediment systems that is not immediately observable in classical impact assessment frameworks. We examine the hidden heterogeneity associated with one of the most ubiquitous coastal modifications; dense swing moorings fields. Using a model based geo-statistical framework we highlight the variation in sedimentology throughout mooring fields and reference locations. Moorings were correlated with patches of sediment with larger particle sizes, and associated metal(loid) concentrations in these patches were depressed. Our work highlights two important ideas i) mooring fields create a mosaic of habitat in which contamination decreases and grain sizes increase close to moorings, and ii) model- based frameworks provide an information rich, easy-to-interpret way to communicate complex analyses to stakeholders. Highlights: Boating infrastructure such as moorings can have an environmental footprint. Effects of moorings on sediment communities not well studied Mooring fields create fine-scale heterogeneity and a mosaic of habitat. Contamination decreases and grain sizes increase close to moorings. Habitat heterogeneity important to consider when adding or removing moorings